Infrared and EPR spectroscopic study of open-shell reactive intermediates: F + NH3 in solid argon: Low-Temperature Physics and Chemistry in Cryomatrice - Misochko, Eugenii Ya.; Goldschleger, Ilya U.; Akimov, Alexander V.; Wight, Charles A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Mobile F atoms react with NH3 molecules in an argon matrix at temperatures T=7√35 K. The open-shell NH2√HF complex was observed by EPR and infrared spectroscopies as the main product of this reaction. The hyperfine constants of the NH2√HF complex aN=1.20 mT, aH=2.40 mT, andaF=0.70 mT were determined from the EPR spectra of samples using NH3, 15NH3 and ND3 isotopomers.Prominent features of the infrared spectrum of NH2√HF are a strongly red-shifted HF stretching mode(Dn≈ - 720 cm-1 relative to that for isolated HF) and strong absorptions at 791 and 798 cm-1 attributedto HF librational modes in the complex. Quantum chemistry calculations reveal that the hydrogen-bonded NH2 √HF complex has a planar C2n structure and a binding energy of 51 kJ/mol. Calculated hyperfine constants and vibrational frequencies of the complex are in good agreement with those observed in the EPR and IR experiments.